Management of ocular sarcoidosis - Baughman, R.P.; Lower, E.F.; Ingledue, et al., R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: A step wise approach to the use of cytotoxic and anti-tumor necrosis factor (TNF) antibodies has been developed for managing chronic sarcoidosis. Objectives: To provide a summary of our experience with immunosuppressive agents especially methotrexate and the anti-tumor necrosis factor antibodies in treating chronic ocular sarcoidosis. Study Design and Methods: This was a retrospective review of 1587 sarcoidosis patients seen at one center over a six year period. All patients with definite or probable ocular sarcoidosis were identified. Results: A total of 465 (29%) of the sarcoidosis patients experienced ocular disease. Of these, 365 patients were treated with methotrexate (MTX) for their eye disease with 281 (77% of those started on MTX) still receiving MTX at the end of the study. Methotrexate was the only systemic therapy prescribed in 115 patients while 101 patients also received concurrent prednisone. Other combinations administered include MTX plus azathioprine and/or leflunomide. A total of 25 patients were treated with the monoclonal anti-TNF antibodies infliximab (19 patients) or adalimumab (6 patients).While all patients initially responded to anti-TNF therapy, only ten patients experienced a sustained response with ongoing therapy or complete remission of ocular disease. Recurrent infections, adverse drug events, or financial constraints were responsible for most drug discontinuations. Conclusion: Most cases of chronic ocular sarcoidosis respond well to immunosuppressive therapy. However, patients may require combination therapy to achieve and maintain disease control. The use of anti-TNF agents for refractory disease is encouraging but can be accompanied by significant toxicity.